On the synthesis of functionalized porphyrins and porphyrin conjugates via β-aminoporphyrins. (17th February 2016) - Abdulaeva, Inna A.; Birin, Kirill P.; Michalak, Julien; Romieu, Anthony; Stern, Christine; Bessmertnykh-Lemeune, Alla; Guilard, Roger; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.
Abstract : A two-step methodology to prepare a series of meso -tetraarylporphyrin conjugates bearing water-soluble moieties, anchoring groups and receptor subunits. Abstract : The synthesis of functionalized porphyrins and their conjugates from meso -tetraarylporphyrins through the acylation and the oxidation of β-aminoporphyrins was investigated. 2, 3-Dioxochlorins were prepared by the oxidation of a variety of β-aminoporphyrins and subsequently used in a condensation reaction with functionalized aromatic aldehydes and ammonium acetate to form β-functionalized porphyrins bearing a fused imidazole ring. Under optimized experimental conditions both reactions tolerate various functional groups and afford the products in an appropriate overall yield. The mildness and usefulness of this methodology are illustrated by several examples including the synthesis of porphyrins bearing receptor groups and water-solubilizing moieties.